Chest Pain Center Accreditation Is Associated With Improved In‐Hospital Outcomes of Acute Myocardial Infarction Patients in China: Findings From the CCC‐ACS Project. Issue 21 (5th November 2019) - Fan, Fangfang; Li, Yuxi; Zhang, Yan; Li, Jianping; Liu, Jing; Hao, Yongchen; Smith, Sidney C.; Fonarow, Gregg C.; Taubert, Kathryn A.; Ge, Junbo; Zhao, Dong; Huo, Yong; et al.
Abstract : Background: Chest pain center (CPC) accreditation plays an important role in the management of acute myocardial infarction (AMI). However, no evidence shows whether the outcomes of AMI patients are improved with CPC accreditation in China. Methods and Results: This retrospective analysis is based on a predesigned nationwide registry, CCC‐ACS (Improving Care for Cardiovascular Disease in China‐Acute Coronary Syndrome). The primary outcome was major adverse cardiovascular events (MACE), including all‐cause death, reinfarction, stent thrombosis, stroke, and heart failure. A total of 15 344 AMI patients, from 40 CPC‐accredited hospitals, were enrolled, including 7544 admitted before and 7800 after accreditation. In propensity score matching, 6700 patients in each group were matched. The incidence of 7‐day MACE (6.7% versus 8.0%; P =0.003) and all‐cause death (1.1% versus 1.6%; P =0.021) was lower after accreditation. In multivariate adjusted mixed‐effects Cox proportional hazards models, CPC accreditation was associated with significantly decreased risk of MACE (hazard ratio: 0.78; 95% CI, 0.68–0.91) and all‐cause death (hazard ratio: 0.71; 95% CI, 0.51–0.99). The risk of MACE and all‐cause death both followed a reverse J‐shaped trend: the risk of MACE and all‐cause death decreased gradually after achieving CPC accreditation, with minimal risk occurring in the first year, but increased in the second year and after. Conclusions: Based on a large‐scale national registry data set, CPC accreditation was associated with better in‐hospital outcomes for AMI patients. However, the benefits seemed to attenuate over time, and reaccreditation may be essential for maintaining AMI care quality and outcomes.